FINITE ELEMENT ANALYSIS OF ENDODONTICALLY TREATED AND NON-ENDODONTICALLY TREATED MANDIBULAR SECOND PRIMARY MOLARS WITH DIFFERENT RESTORATIONS - Özgün Sunar; Tuğba Yildirim; Arife Kaptan (Clinical Dentistry and Research, 2026)
Background and Aim: The biomechanical behavior ofrestorations under forces may affect the treatment success.The aim was to evaluate the stress distribution in endodonticallytreated and non-endodontically treated mandibular deciduoussecond molars restored with different crown materials (stainlesssteel crown (SSC), pediatric zirconia crown (PZC) and glass fibercrown (GFC)) by using finite element analysis (FEA).Materials and Methods: A virtual tooth geometry wascreated in Solidworks software using a computed tomographyimage of the tooth. The root canal of the deciduous tooth wasfilled with zinc oxide eugenol cement to simulate endodontictreatment. In order to analyse the stress on the obtainedmodels caused by different crown materials (SSC, PZC, GFC), aforce of 200 N was applied to the tooth crown as normal andoblique in ANSYS Workbench R22 software. Overall, twelvefinite element models were developed and analyzed in termsof maximum von Mises stress and maximum deformation.Results: Stress levels in the models under oblique loading werehigher than those under normal loading conditions. Regardingthe crown material, PZC was subjected to the highest stressunder all loading conditions, while the average lowest stresswas found in GFC. In endodontically treated models, rootstress levels were found to be 1000 times higher than inmodels without endodontic treatment. GFC showed higherdeformation values than other crowns.Conclusion: SSC exhibited lower maximum von Mises stressthan PZC and lower deformation than GFC in most analyses.SSC can be considered a suitable material for endodonticallytreated primary second molars.